Answer:
D. -x2 + 2x -3
Step-by-step explanation:
the first step is we open all the brackets then it will be :
x2 - 3x - 2x2 + 5x - 3
= x2 - 2x2 - 3x + 5x - 3
= -x2 + 2x -3
Answer:
vertex = (- 1, 1 )
Step-by-step explanation:
Given a parabola in standard form
y = ax² + bx + c ( a ≠ 0 )
Then the x- coordinate of the vertex is
x = - 
y = x² + 2x + 2 ← is in standard form
with a = 1 and b = 2 , then
x = -
= - 1
substitute x = - 1 into the equation for y- coordinate of vertex
y = (- 1)² + 2(- 1) + 2 = 1 - 2 + 2 = 1
vertex = (- 1, 1 )
Answer:
ur correct u got it.
Step-by-step explanation:
I forget how to do this. I haven't done this in awhile.